Utilitarian diversity of Senna occidentalis in Benin, West Africa: Ethnobotanical insights and sustainable management - Idohou, Alix Frank Rodrigue; Wouyou, Hyacinthe; Agbangba, Emile; Dossou, Anael (Ethnobotany Research and Applications, 2025)
Background: Senna occidentalis (L.) Link is a medicinal plant whose therapeutic properties have been widely appreciated in medicinal preparations throughout the world. This study investigates the indigenous knowledge and use of S. occidentalis throughout Benin. Methods: The study was carried out in nine communes of Benin. From September to November 2023, semi-structured interviews were conducted in 72 villages, involving 195 respondents from 14 different sociolinguistic groups. Cramer’s test was used to determine the degree of relationship between socio-linguistic groups and the forms and parts of the plant used. In addition, a Correspondence Analysis (CA) was performed to examine variations in species consensus values. Results: Our results showed that the species is primarily used for medicinal purposes (93.57%), with smaller proportions allocated to food (3.21%) and medico-romantic applications (3.21%). The uses of the species varied with socio-linguistic affiliation. Decoction (71.88%), infusion (7.63%), toothpick (6.42%) and trituration (6.02%) were the forms mainly used by the local population. The leaves (71.08%) were the most commonly used part of the plant. Roots (20.08%) and seeds (8.83%) were used, but to a lesser extent. In addition, leaves and roots were mainly used parts of the species to treat malaria and typhoid fever, while seeds were used for constipation. Conclusions: These results demonstrate the medicinal importance of S. occidentalis in Benin and suggest the need for priority actions for the sustainable management and use of the species. Further research on the medicinal components of different parts of the plant could aid its promotion and valorization. Keywords: Ethnobotany; Asteraceae, Indigenous communities; Human diseases, Herbal medicine